Individual, social and environmental determinants of smokeless tobacco and betel quid use amongst adolescents of Karachi: a school-based cross-sectional survey - Azmina Hussain; Sidra Zaheer; Kashif Shafique (BMC, 2017)
Abstract Background With 600 million people using betel quid (BQ) globally, and smokeless tobacco (SLT) use being more wide-spread; the duo is an uphill public health concern in South Asian countries. SLT and/or BQ use increases the risk for morbidity and mortality from oral cancer. Because SLT and/or BQ use is initiated during adolescence, it renders this group more vulnerable; and particular attention is needed to curb SLT and/or BQ use to reduce related disease burden. We aimed to observe the differential individual, social and environmental features amongst SLT and/or BQ users to determine the key influencers of its use in adolescents. Methods This study was a cross-sectional survey of 2140 adolescents from secondary schools of Karachi, Pakistan. The main outcome measure was SLT and/or BQ use based on their consumption in the past 30 days. Univariate and multivariate regression binary logistic analyses were employed while reporting results in both crude form and adjusted odds ratio (after adjusting for all remaining individual, social and environmental level variables) with 95% confidence level. A p-value of < .05 was considered significant for all analyses. Results The overall prevalence of SLT and/or BQ use was 42.6% (n = 912) of the total sample. The SLT and/or BQ consumer group had more males than females. A significant proportion of user (n = 558, 61.2%) was found in co-education schools. Students whose peers (OR = 6.79, 95% CI 4.67-9.87, p-value <0.001) and/or either of the parents (OR = 2.16, 95% CI 1.73-2.65, p-value <0.001) used SLT and/or BQ, alongside, adolescents who had not attended knowledge based sessions in schools regarding harmful effects of SLT and/or BQ were more likely to consume it. It's availability with outside school hawkers increased the odds of its use by 6 times, as indicated by both univariate and multivariate models after adjusting for the remaining variables. Conclusion In conclusion, students studying in co-education, parents and peers use, lack of knowledge based sessions on harmful health effects of SLT and/or BQ, and easy availability of the product from hawkers outside school all contribute towards enhanced risk of SLT and/or BQ use in adolescents.